2023
DOI: 10.1039/d2sc06977f
|View full text |Cite
|
Sign up to set email alerts
|

Radiometallation and photo-triggered release of ready-to-inject radiopharmaceuticals from the solid phase

Abstract: The efficient, large-scale synthesis of radiometallated radiopharmaceuticals represents an emerging clinical need which, to date, is inherently limited by time consuming, sequential procedures to conduct isotope separation, radiochemical labeling and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“… 154 To visualize liposome distribution and their accumulation sites, a 99m Tc-radiolabeled liposomal platform was employed by Silindir-Gunay et al for molecular tumour imaging SPECT and CT. 155 In principle, NCs such as liposomes can be labeled by indirect labeling that involves attaching a radiolabeled molecule (such as a chelator or a targeting ligand) to the surface of previously prepared NCs using conjugation chemistry 156 or by direct labeling via incorporating a radiolabeled ligand or chelator to label metal radionuclides into the NC's surface during the preparation. 157 The authors reported neutral and positive charged FA-conjugated and PEGylated DTPA-PE containing liposomes ( Fig. 11I ).…”
Section: Folic Acid (Fa)-conjugated Nanocarriersmentioning
confidence: 95%
“… 154 To visualize liposome distribution and their accumulation sites, a 99m Tc-radiolabeled liposomal platform was employed by Silindir-Gunay et al for molecular tumour imaging SPECT and CT. 155 In principle, NCs such as liposomes can be labeled by indirect labeling that involves attaching a radiolabeled molecule (such as a chelator or a targeting ligand) to the surface of previously prepared NCs using conjugation chemistry 156 or by direct labeling via incorporating a radiolabeled ligand or chelator to label metal radionuclides into the NC's surface during the preparation. 157 The authors reported neutral and positive charged FA-conjugated and PEGylated DTPA-PE containing liposomes ( Fig. 11I ).…”
Section: Folic Acid (Fa)-conjugated Nanocarriersmentioning
confidence: 95%
“…83 Our group addressed this problem by using traceless photocleavage of a fully assembled radiopharmaceutical from a water-compatible solid support (Figure 5). 84 A photoreactive, unnatural amino acid, 3-amino-3-(2-nitrophenyl)propionic acid (ANP), was introduced between the resin and the chelatepeptide construct. This approach is well established for the ablation and subsequent analysis of resin-appended peptides using matrix-assisted laser desorption/ionization (MALDI) but is also compatible with UV (365 nm) irradiation for release from the resin in an aqueous suspension.…”
Section: Radiosynthesis On a Solid Support: Photolysismentioning
confidence: 99%